Genotypic and Phenotypic Characterization of Enterotoxigenic Escherichia coli Strains Isolated from Peruvian Children - Rivera, F. P. (2014)
Enterotoxigenic Escherichia coli (ETEC) is a major cause of childhood diarrhea. The present study sought to determine the prevalence and distribution of toxin types, colonization factors (CFs), and antimicrobial susceptibility of ETEC strains isolated from Peruvian children. We analyzed ETEC strains isolated from Peruvian children between 2 and 24 months of age in a passive surveillance study. Five E. coli colonies per patient were studied by multiplex real-time PCR to identify ETEC virulence factors. ETEC-associated toxins were confirmed using a GM1-based enzyme-linked immunosorbent assay. Confirmed strains were tested for CFs by dot blot assay using 21 monoclonal antibodies. We analyzed 1,129 samples from children with diarrhea and 744 control children and found ETEC in 5.3% and 4.3%, respectively. ETEC was more frequently isolated from children >12 months of age than from children <12 months of age (P < 0.001). Fifty-two percent of ETEC isolates from children with diarrhea and 72% of isolates from controls were heat-labile enterotoxin (LT) positive and heat-stable enterotoxin (ST) negative; 25% and 19%, respectively, were LT negative and ST positive; and 23% and 9%, respectively, were LT positive and ST positive. CFs were identified in 64% of diarrheal samples and 37% of control samples (P < 0.05). The most common CFs were CS6 (14% and 7%, respectively), CS12 (12% and 4%, respectively), and CS1 (9% and 4%, respectively). ST-producing ETEC strains caused more severe diarrhea than non-ST-producing ETEC strains. The strains were most frequently resistant to ampicillin (71%) and co-trimoxazole (61%). ETEC was thus found to be more prevalent in older infants. LT was the most common toxin type; 64% of strains had an identified CF. These data are relevant in estimating the burden of disease due to ETEC and the potential coverage of children in Peru by investigational vaccines.